PENEKANAN ANGGARAN SEBAGAI PEMODERASI PENGARUH PARTISIPASI PENGANGGARAN DAN ASIMETRI INFORMASI PADA SENJANGAN ANGGARAN - Sari, Ni Made Lamita; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2017)
This research aims to determine the of budget emphasis moderating effect of budgetary participation and information asymmetry on budgetary slack. Research is located in community bank or Bank Perkreditan Rakyat (BPR) Gianyar regency. The sample was selected by using purposive sampling which a sample of 19 BPR with 86 respondents. Data testing regression moderating analysis (MRA). The analysis showed that the budget emphasis not as a moderating the effect of budgetary participation on the budgetary slack in BPR Gianyar. Meanwhile, the budget emphasis to be a moderating the effect of information asymmetry on budgetary slack. Hypothesis testing results showed that the higher the information asymmetry leads to higher budgetary slack, especially when budget emphasis high.
Keywords: budgetary participation, information asymmetry, budget emphasis, budgetary slack